2001
DOI: 10.1521/bumc.65.4.522.19841
|View full text |Cite
|
Sign up to set email alerts
|

A therapeutic nursery evaluation study

Abstract: The object of this prospective study was to evaluate the effectiveness of a therapeutic nursery program for troubled preschoolers attending the Preschool Day Treatment Center of The Menninger Clinic. Thirty-eight seriously disturbed preschoolers were assessed both at admission and at 9 months or at discharge (if before 9 months) in a pre-post design. Commonly used assessment instruments were collected by independent research clinicians. Significant gains were found in both internalizing and externalizing behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…In 1 Canadian study, Grizenko and colleagues found significant improvement in externalizing problems of children who attended their 4-month program. 21 Similar findings were found with elementary-age children, 19,22,23 preschoolers, 24,25 and adolescents. 26 28 Some studies have found little to no effect though.…”
Section: Introductionsupporting
confidence: 83%
“…In 1 Canadian study, Grizenko and colleagues found significant improvement in externalizing problems of children who attended their 4-month program. 21 Similar findings were found with elementary-age children, 19,22,23 preschoolers, 24,25 and adolescents. 26 28 Some studies have found little to no effect though.…”
Section: Introductionsupporting
confidence: 83%
“…In a recent review of psychiatric day and partial hospital treatment programs for preschoolers, Tse (2006) noted that empirical attention to the effectiveness of preschool day treatment programs has been quite limited, with only five studies providing quantitative analysis of treatment outcomes. Findings from these studies were somewhat mixed, with some describing positive treatment gains (Culp, Little, Letts & Lawrence, 1991;Oates, Gray, Schweitzer, Kempe & Harmon, 1995;Ware, Novotny & Coyne, 2001), others suggesting little benefit (Richman, Graham & Stevenson, 1983), and still others suggesting that day treatment may benefit some children more than others, with both child and family factors influencing outcomes (Cohen, Bradley & Kolers, 1987).…”
Section: Psychiatric Partial Hospitalization For Young Childrenmentioning
confidence: 99%